Family Vs. Non-Family Business Owners’ Commitment to Their Town - Assaker, Guy (2013)
This study examines differences between family-owned and non-family-owned small and medium tourism enterprises (SMTEs) operating in regional tourism destinations. The research focuses on SMTE owners' commitment to stay in the town in which they are embedded. Based on samples of family (N = 157) and non-family (N = 141) businesses in regional South Australia, was used to test the construct validity of SMTE owners' “commitment to stay”. Multigroup invariance was used to test the factorial equivalence of scores from the commitment model across family and non-family businesses. Results support the validity of the “commitment to stay” CFA model. Multigroup invariance analysis suggests family business owners have a greater commitment to staying in their town. These results contribute to our understanding of the unique objectives and behaviours of family businesses in tourism as well as present important implications to destination managers aiming to support sustainable entrepreneurial development.